The age of Jihad : Islamic State and the great war for the Middle East - Cockburn, Patrick, 1950- (New York : Verso, 2016)
'Presented in ... diary form, this substantial volume draws together a careful selection of Cockburn's writings from the frontlines of the conflicts in Afghanistan, Iraq, Libya and Syria, interspersed with thoughtful analyses and contemporary, original reflection. What emerges is the fine grain and nuance of an unfolding tragedy in which, in contrast to the often facile proclamations of politicians and much of the media:'These are not black-and-white situations, good guys against bad, vile tyrant against a risen people like a scene out of Les Miserables. It is astonishing and depressing to see Western governments committing their countries to wars without recognizing this basic fact.' The conflicts being fueled by such misunderstandings are today spilling over to cities in the West, provoking a backlash that learns little from recent history and is likely only to make things worse.--Publisher.
Part 1. Afghan prelude : The overthrow of the Taliban: Afghanistan, 2001 --Part 2. The occupation of Iraq : Iraq under sanctions: Iraq, 1990-2003 --Iraq under sanctions, Iraq, 2003 --Regime change: Iraq, 2003 --Resistance: Iraq, 2004 --Bombs and ballots: Iraq, 2005 --Civil war: Iraq, 2006-7 --Drawdown: Iraq, 2007-10 --Part 3. Afghan reprise : The return of the Taliban: Afghanistan, 2009-12 --Part IV: The Arab Spring : Mission creep: Libya, 2011 --The'Somalianisation' of Libya: Libya, 2012-14 --Yemen in the crossfire: Yemen, 2009-15 --Sectarian venom: Bahrain, 2011 --Part 5. Syria: revolution and counter-revolution : From revolution to sectarian war: Syria, 2011-13 --Syrian catastrophe: Syria, 2013-14 --Part 6. Birth of a caliphate : Ten years on: Iraq, 2013 --Iraq on the brink: Iraq, 2013-2014 --The Islamic State expands: The Caliphate, 2014 --The Islamic State remains: The Caliphate, 2014-2015 --Life in the Caliphate: The Caliphate, 2015 --The Islamic State at bay: The Caliphate, 2015-2016 --Afterword : Eight wars.
Sumbangan Mohamad Taha (2017).
Koleksi sumbangan Dr Mohamad Nasrin Mohamad Nasir.
Keywords: IS (Organization) -- History; Iraq War, 2003-2011 -- Social aspects; Sunnites -- Iraq; Shiites -- Iraq; Islam and politics -- Iraq; Jihad -- History; Middle East -- History -- 21st century